Improving Indonesian Soft Power Through Cultural Exchange in Thailand: Rajamangala University of Technology Krungthep Summer Semester Program in 2024 - Handayani, Wiwik; Prameswari, Nur Shadrina; Ariyanto, M. Idris; Kusumaningsih, Intan (Unram Journal of Community Service, 2025)
This research discusses efforts to preserve Indonesian culture through the Summer Semester program held at Rajamangala University of Technology Krungthep, Thailand. The main focus of this activity is to exchange Indonesian culture as a form of cultural diplomacy and increase Indonesia's soft power in the international arena. Through this activity, Indonesia can introduce cultural values ​​and traditions to the global community, which contributes to strengthening Indonesia's positive image in the eyes of the world. This activity not only functions as a means of cultural promotion, but also as a medium for education and cultural exchange between nations, allowing participants from various backgrounds to learn and interact directly with Indonesian culture for participants from various countries